Keterlibatan Siswa ditinjau dari Jenis Kelamin dan Jenjang Kelas pada Siswa SMK di SMK N 3 Jepara - Verdina, Nurul Verry; Pramono, Ridwan Budi (Indonesian Journal of Educational Counseling, 2025)
Student engagement is defined as the active participation of students in the learning process, including affective, cognitive, and behavioral dimensions. High levels of student engagement contribute to positive academic outcomes as high engaged students tend to be more involved and accountable in their learning. In contrast, students with low student engagement often feel dissatisfied with their educational experience and are at high risk of dropping out of school. The dropout phenomenon in Indonesia shows the highest rate among senior secondary/vocational students. This study aims to examine the relationship between student engagement based on gender and grade level, and look at the differences. This study used quantitative methods with a correlational and comparative approach, involving 99 students from SMK N 3 Jepara. The instrument used was the USEI scale, which was adapted and data processing using the SPSS bootstrap method. The results showed that the majority of students' engagement was in the moderate category (41 students), followed by the high (32 students) and low (26 students) categories. No significant relationship was found between student engagement and class, but there was a significant relationship with gender, where female students showed higher level of student engagement, especially in the cognitive engagement aspect.